HIGHER EDUCATION REFORMS IN CHINA: MODERN TRENDS ANDDEVELOPMENT PROSPECTS (1992-2022) (Universal International Scientific Journal, 2026)
Higher education solves such basic tasks as training highly qualifiedspecialists,developing science, technology and culture, and promoting social development. The article,based on documentary and historiographical sources, analyzes the process of reforming highereducation in China from 1992 to 2022 and the efforts of its institutions, reveals the dynamics ofgrowth in the number of universities and the number of students, and notes the specifics andcomplexities of the process. The stages of higher education reform are highlighted and their content isrevealed, China's efforts to create key universities and introduce new academic disciplines (“Project211”, “Project 985”, “Double First Class Project “ are highlighted.
Keywords: China; higher education reform; quantitative and qualitative indicators of higher school reform